An approach to joint roughness measurement in Rock-A comparative study - Mohd. Amin, Mohd. For; Mustaffar, Mushairry (Universiti Teknologi Malaysia, 2001)
The shear strength of a weakness plane in rock such as joint, is greatly influenced by its surface condition. Therefore, surface texture and degree of roughness are important aspects to be considered in assessing the shear strength of joint. However, the present method for measuring surface texture are labourious and time consuming processes. This study highlights an alternative method of measurement using close-range photogrammetry. The suitability of the proposed method was verified in laboratory using a physical model of joint surface. The degree of roughness of the model surface, was measured using both photogrammetry and conventional method. All measurements were made on the same grid points marked on the model surface. Data obtained from both methods was compared in terms of peak and through height, profile shape, 3-dimensional plot and roughness index (i.e. standard deviation, absolute roughness and central line average). In the comparison process, data obtained using conventional method is used as reference. To verify its practically, the proposed method was used to measure joint surface in the field. The outcome of this study, clearly shows that photogrammetry exhibits several positive characteristics as an alternative method for measuring surface texture of joint in rock. The use of digital camera allows for a larger amount of field data to be collected and this data could be stored and processed at a later stage. Consequently, this facilities joint survey work in the field. In addition, the 3-dimensional image of the joint surface which can be readily plotted using photogrammetry data, serves as a useful tool in providing vital information on the texture of the joint surface. The image can be used as tool in assessing the surface conditions, which is an important procedure for laboratory shear test on joint in rock.